Metamorfosi queer: Diritti plurali, pratiche di resistenza e desiderio di soggettivazione nel teatro di ricci/forte - Vecchia, Andrea (Mimesis Journal, 2022)
The desire as the presence of a lack. The heterosexual symbolic apparatus as a hierarchical paradigm. The body materiality as a space of unexpected meanings. The performatization of the genre. The hermeneutic issues in the shows of the ricci / forte ensemble are numerous: the bodies have a destabilizing, excessive ostension, torn by normative ghosts and violent political speeches. In this study we intend to highlight in the theater of ricci / forte the presence of identity constriction processes of contemporary society, told by performers similar to liminary creatures, far from regulatory paradigms and the imposition of modeling. The study investigates how ricci / forte – with an attack on the symbolic and the imaginary – deny the founding roles and cultural archetypes of the West. Their original post-dramatic iconoclasm fights the male / female polarization, the dominant patriarchal social structure, seeking the truth about the construction of the subject’s desire.